Structural parameters and comparative analysis of the performance of four beetle elytron plate walls - Li, Yinsheng; Hu, Liping; Chen, Jinxiang; Sheng, Canjun (Journal of Civil Engineering and Management, 2024)
This article presents the characteristics of four straw-filled beetle elytron plate (BEPsc) nonload-bearing walls, with their thermal and mechanical properties ascertained by the finite element method, focusing on structural parameters reported in previous studies and further optimized in this paper. The results are as follows: 1) The sequence of the four models’ mechanical and thermal insulation properties with the reported structural parameters is given. The mechanical properties are mainly affected by the core layer’s out-of-plane bending moment of inertia Ix. The insulation capability is mainly governed by the minimum cross section of the core concrete. Based on this result, a BEP with nonuniform cross-sectional honeycomb walls is proposed. 2) Further optimization is conducted on the two models with the weakest mechanical and thermal properties. The I-beam beetle elytron plate (IBEPsc) is proven most suitable for nonload-bearing walls. The potential for end-trabecular beetle elytron plate (EBEPsc) in hollow floors is expected. 3) As biomimetic models emerge constantly, it is of great significance to conduct parallel comparisons between new and old models to determine their performance levels and advantages. This paper provides an example for selecting suitable BEPs for applications and an inspiration for more work on screening outstanding biomimetic models.